Experience with propafenone for the treatment of cardiac arrhythmias in children - Çeliker, Alpay; Özer, Sema; Özme, Şencan; Özkutlu, Süheyla; Kahramanyol, Öz (The Turkish Journal of Pediatrics, 1990)
The aim of this prospective study was to evaluate the efficacy of propafenone in suppressing various arrhythmias in a group of children who were patients in the Pediatric Cardiology Unit of Hacettepe University Children’s Hospital. Seven of the 13 children (53.8%) with ventricular ectopics, all three children with paroxysmal re-entry atrioventricular tachycardia, and two of the three children with paroxysmal atrial tachycardia were treated successfully with propafenone. The drug did not cause any side effects or arrhythmogenesis. The median dosage of propafenone at discharge was 300 mg/m²/day (range 250-400 mg/m²/day) every eight hours. Our findings confirm the efficacy and safety of propafenone for the treatment of childhood arrhythmias.